The Effect of Yoga Exercise on Reducing Blood Pressure among Elderly with Hypertension : a Systematic Review - Permana, Bhakti; Lindayani, Linlin; Hendra, Agus; Juniarni, Lia (JURNAL PENDIDIKAN KEPERAWATAN INDONESIA, 2020)
ABSTRACTHypertension is the most commonly encountered problems experienced by the elderly with sometimes unknown cause. One effort to lower blood pressure in the elderly is to provide yoga exercises, where yoga exercises can stimulate endorphin hormone expenditure. The purpose of review was to determine the effectiveness of yoga exercises for decreasing blood pressure in the elderly. An initial search for articles was done on Google Scholar and PubMed. Studies obtained about exercise therapy for hypertension elderly have 4,560 articles / journals but only 5 articles meet the search criteria. According to the search results, yoga exercises can reduce blood pressure in the elderly. Besides, it is also very important to be applied as a non-pharmacological therapy for the elderly who have a medical history of hypertension. It is expected that health professionals can recommend this as a therapy for lowering blood pressure in the elderly.Â Â ABSTRAKHipertensi adalah masalah yang paling sering ditemui yang dialami oleh lansia dengan penyebab yang terkadang tidak diketahui. Salah satu upaya menurunkan tekanan darah pada lansia adalah dengan memberikan senam yoga, dimana senam yoga dapat merangsang pengeluaran hormon endorphin. Tujuan review adalah untuk mengetahui keefektifan senam yoga dalam menurunkan tekanan darah pada lansia. Pencarian awal untuk artikel dilakukan di Google Scholar dan PubMed. Studi tentang terapi senam lansia hipertensi didapatkan 4.560 artikel / jurnal tetapi hanya 5 artikel yang memenuhi kriteria pencarian. Menurut hasil pencarian, senam yoga dapat menurunkan tekanan darah pada lansia. Disamping itu juga sangat penting diterapkan sebagai terapi non farmakologi bagi lansia yang memiliki riwayat kesehatan hipertensi. Diharapkan tenaga kesehatan dapat merekomendasikan hal ini sebagai terapi penurunan tekanan darah pada lansia.Â